Issues of Intruder Analytical Model Applicability for Evaluating an Efficiency of Security Systems; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Bukovetskiy A. V. Anton; Boyko (Boiko) V. I. Vladimir Ilyich; Kolpakov G. N. Gennadiy Nikolaevich; Poner M. V. Michael (2016, 2016)
Title screen